Copyright issues in digital libraries - Đinh, Thúy Quỳnh (2020)
The research starts with an introduction of some legal documents on copyright in library operations in general and digital libraries in particular then goes into the details of enforcement copyright in digital libraries in Vietnam. Lastly, on the basis of the findings, the author proposes some suggestions for efffective enforcement of copyright in Vietnam's digital libraries